Effect of Ethanol Solution Concentration in the Extraction Process of Centella asiatica L. Bioactive Components Using Microwave-Assisted Extraction (MAE) Method - Fira Ulvatur Rohmah; Rina Auliyah Safitri; Ayu Ulum Rahmawati; Atiqa Rahmawati (Program Studi Teknik Kimia Universitas Jember, 2022)
The Pegagan plant has a scientific name in the form of Centella asiatica L. which is included in the Centella genus, Apiaceae family, and kingdom Plantae. Pegagan (Centella asiatica L.) has distinctive bioactive components, namely triterpene ester glycoside compounds in the form of asiaticoside and madecassoside, and triterpene group compounds in the form of Asiatic acid and madecassic acid. In this study, the extraction of bioactive components from pegagan was carried out using the Microwave-Assisted Extraction (MAE) method and will study the effect of ethanol solvent concentration in the extraction of bioactive compounds. Analysis of the extracted bioactive content was carried out by analyzing the total phenol content using the Folin-Ciocalteau reagent and ANOVA analysis. The results obtained from the study were in the form of total phenol content as an indication of the presence of bioactive compounds, namely at operating conditions of 450 watts of power, 50% ethanol concentration with a radiation time of 15 minutes which resulted in a total phenol content of 21.9244 mg AGE/g sample. In the ANOVA analysis with ethanol solvent, variables that gave a significant response to the total phenol content were microwave power, radiation time, and ethanol concentration with an R-square value of 95.31%. The effect of ethanol concentration on the total phenol content produced, namely the concentration of pure ethanol solvent will produce extracts with the smallest total phenol content, the effect of extraction time on total phenol content, namely the longer extraction time will increase the total phenol content. Maximum total phenol content using ethanol solvent that is, at operating conditions of 450 watts of power, 10% ethanol concentration with a radiation time of 15 minutes which resulted in a total phenol content of 520 mg AGE/g sample.